Production of particleboard using new formulation melamine erea formaldehyde adhesive for low formaldehyde emission - Loh, Yang Way (2011)
Particleboard is an engineered wood panel product consisted of particle bonded with formulated adhesives together with heat and pressure. In recent years, air pollution had become a concerning issue around the globe, as formaldehyde was classified as a type of carcinogen which can cause cancer. Urea formaldehyde (UF) is a common type of adhesive which used as a binder for production of particleboard. However, studies found out that the amount of formaldehyde emitted from particleboard bonded with UF was higher. With the stringent enforcement in air pollution, other types of adhesives were introduced as binder of particleboard, including melamine urea formaldehyde (MUF) resin. The aim of this study is to determine the physical and mechanical properties and formaldehyde emission from the application of MUF resin in particleboard production. In this study, two phases of study were carried out. For the initial phase, the effect of surface-to-core ratio, which is the amount of fine particle and thick flake respectively in three-layered particleboard, was studied. Five different ratios were applied to manufactured particleboard, which were 70% core and 30% surface; 60% core and 40% surface; 50% core and 50% surface; 40% core and 60% surface; and 30% core and 70% surface. The temperature applied was 180°C and pressing time was 10.5 minutes by using RD 111 as the MUF resin. From this study, particleboard with 60% core and 40% fine was observed to provide the optimum result for strength properties and lowest formaldehyde emission. For the second phase of this study, all particleboards were produced with 60% core and 40% fine. Three MUF resins were prepared in different melamine content, which were 14.8%, 19.1% and 13.0% for RD 111, RD 114 and RD 218 respectively. Three different pressing temperatures was applied for each MUF resin, which were 170°C, 180°C and 190°C respectively, and three different pressing times of 9.5 minutes, 10.5 minutes and 11.5 minutes were applied for each pressing temperature. This study showed that MUF resins with different melamine content interacted significantly with pressing time and pressing temperature. RD 218 with lowest melamine content of 13.0% provided the optimum strength properties and formaldehyde emission. In short, all MUF-bonded particleboard obtained Super E0 (F****) classification according to JIS A 1460, with the average formaldehyde emission ranged from 0.08mg/L to 0.18mg/L. All particleboard produced complied JIS A 5908 for strength properties, except for particleboard bonded with RD 114 resins recorded some undesired strength properties.